KINERJA KUALITAS PELAYANAN PERIZINAN GANGGUAN USAHA DI KANTOR PELAYANAN PERIZINAN TERPADU KOTA GORONTALO - Sarfan Dj Tabo (LL-DIKTI Wilayah IX Sulawesi, 2018)
Performance Optimalisasi of aparatur for ever to improve the quality of goodness of aparatur quality and also itself giving of service. In anticipating constraint in Inwrought Peleyanan Permit hence done some step that is maximizing process service of permit to society either from service procedure facet, aparatur, and medium of prasana. According to Gronroos expressing the quality of service cover the Quality of function, Technical quality, Reputation Company. the prima Service will push society follow to participate in course of development.